2021
DOI: 10.1155/2021/5806602
|View full text |Cite
|
Sign up to set email alerts
|

SPP1 Promotes Enzalutamide Resistance and Epithelial‐Mesenchymal‐Transition Activation in Castration‐Resistant Prostate Cancer via PI3K/AKT and ERK1/2 Pathways

Abstract: The bottleneck arising from castration-resistant prostate cancer (CRPC) treatment is its high metastasis potential and antiandrogen drug resistance, which severely affects survival time of prostate cancer (PCa) patients. Secreted phosphoprotein 1 (SPP1) is a cardinal mediator of tumor-associated inflammation and facilitates metastasis. In our previous study, we firstly revealed SPP1 was a potential hub signature for predicting metastatic CRPC (mCRPC) development. Herein, we integrated multiple databases to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 29 publications
(37 reference statements)
2
26
0
Order By: Relevance
“…SPP1, also termed osteopontin (OPN), is an important extracellular glycoprotein in the small integrin-binding ligand N-linked glycoprotein (SIBLING) family (47). Much research has shown that SPP1 is closely linked with processes such as growth, adhesion, invasion, angiogenesis, and metastasis in many malignant tumors (48)(49)(50). In liver cancer cells, SPP1 can not only bind to CD44 and activate the PI3K/Akt signaling pathway, but it can also activate integrins and induce the expression of NF-κB to inhibit apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…SPP1, also termed osteopontin (OPN), is an important extracellular glycoprotein in the small integrin-binding ligand N-linked glycoprotein (SIBLING) family (47). Much research has shown that SPP1 is closely linked with processes such as growth, adhesion, invasion, angiogenesis, and metastasis in many malignant tumors (48)(49)(50). In liver cancer cells, SPP1 can not only bind to CD44 and activate the PI3K/Akt signaling pathway, but it can also activate integrins and induce the expression of NF-κB to inhibit apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the combination of OPN, HIFtargeted therapies may have clinical significance, while targeted inhibition of OPN, VEGF and HIF-OPN regulates the expression of EMT-related proteins. EMT is the process by which epithelial cells lose intercellular junctions and apical-basal polarity and transition to mesenchymal cells, and this transition induces epithelial cells to acquire fibroblastic properties that promote cell motility and the formation of new membrane protrusions, and this is a key event in the acquisition of migratory and invasive capacity by cancer cells of epithelial origin [24]. E-cadherin, an important adhesion molecule that maintains epithelial cell junctions and is a specific protein representing the epithelial cell phenotype, is expressed at reduced levels in EMT; similarly, N-cadherin, Vimentin -catenin, which are specific proteins for the mesenchymal cell phenotype, are expressed at elevated levels in EMT [24,42].…”
Section: Opn and Cancer Progression: I Signal Traffic N Downstream Ca...mentioning
confidence: 99%
“…EMT is the process by which epithelial cells lose intercellular junctions and apical-basal polarity and transition to mesenchymal cells, and this transition induces epithelial cells to acquire fibroblastic properties that promote cell motility and the formation of new membrane protrusions, and this is a key event in the acquisition of migratory and invasive capacity by cancer cells of epithelial origin [24]. E-cadherin, an important adhesion molecule that maintains epithelial cell junctions and is a specific protein representing the epithelial cell phenotype, is expressed at reduced levels in EMT; similarly, N-cadherin, Vimentin -catenin, which are specific proteins for the mesenchymal cell phenotype, are expressed at elevated levels in EMT [24,42]. The EMT transcription factors (EMT-TFs) such as Snail, Twist and Slug are key inducers of EMT development, and they are involved in EMT development by suppressing E-cadherin expression and promoting N-cadherin, V -catenin expression, which in turn promote cancer metastasis and invasion [43,44].…”
Section: Opn and Cancer Progression: I Signal Traffic N Downstream Ca...mentioning
confidence: 99%
See 1 more Smart Citation
“…SPP1, an important extracellular matrix component secreted by multiple kinds of cell types including immune cells, fibroblasts, osteoclasts, smooth muscle, and epithelial cells, is overexpressed in many types of tumors [ 107 , 108 ] . In the GSE32269 dataset, SPP1 expression was shown to be significantly higher in the mCRPC group than in the primary PCa group.…”
Section: Drug Resistance In Mcrpcmentioning
confidence: 99%